Intracranial elastance is increased in idiopathic intracranial hypertension. (21st September 2017) - Chisholm, J. T.; Sudhakar, P.; Alhajeri, A. N.; Smith, J. H.
Abstract : Background and purpose: To date, no pathophysiological model has sufficiently accounted for all the findings encountered in patients with idiopathic intracranial hypertension (IIH). Intracranial elastance is an index of volume‐buffering capacity known to play a role in certain disorders of cerebrospinal fluid (CSF) dynamics, which has not been previously investigated in relation to IIH patients. Methods: This was a single‐center retrospective cohort study from 1 July 2011 to 1 July 2016. Values for opening pressure ( P O ), closing pressure ( P C ) and volume ( V ) of CSF removed were collected, as well as demographic and clinical covariates. Intracranial elastance ( E ) and pressure−volume index (PVI) were calculated according to established equations: E = ( P O − P C )/ V and PVI = V /log10 ( P O / P C ), respectively. Those with an alternative central nervous system pathology, including meningitis, encephalitis and normal pressure hydrocephalus were excluded. Eligible patients were subdivided into two groups based on final diagnosis: a control group and an IIH group. Results: In our cohort ( n = 49), a significant association of both E ( P < 0.0001) and PVI ( P = 0.005) with a diagnosis of IIH was observed. Median E was 0.45 [interquartile range (IQR) 0.29–0.63] in the control group and 1 (IQR 0.59–1.29) in the IIH group, and median PVI was 98.07 (IQR 59.92–135.86) in the control group and 64.1 (IQR 42.4–91.7) in the IIH group. Neither E nor PVI were significantly associated with age, gender or body mass index. PVI was independent of opening pressure. Conclusions: As calculated by clinically accessible indices, our study provides evidence that intracranial elastance is increased in IIH, reflecting a novel insight into disease pathogenesis.